Comparative efficacy of Chinese patent medicines in patients with carotid atherosclerotic plaque: a Bayesian network meta− analysis - Wenquan Su; Xiaolong Xie; Jiping Zhao; Qinhua Fan; Naijia Dong; Qingxiao Li; Yawei Du; Shengxian Wu (Chinese Medicine, 2023)
Abstract Background Traditional Chinese patent medicines (TCPMs) have been widely used to treat carotid atherosclerotic plaque (CAP) in China. However, systematic evaluation of the clinical efficacy of TCPMs for CAP is still unknown, and the comparative efficacy of different TCPMs is unclear. Objectives This study aims to compare and rank the effectiveness and safety of different TCPMs in treating CAP using a Bayesian network meta− analysis (NMA). Methods This NMA was performed according to the Preferred Reporting Items for Systematic Reviews and Meta− Analyses (PRISMA) Extension Statement. Eight databases were searched from their inception to August 2023 for randomized controlled trials (RCTs). The articles regarding eligibility and extracted data were screened independently by two authors. The Cochrane Risk of Bias tool was used to evaluate quality and bias. The change of carotid artery intimal− medial thickness (IMT), carotid maximal plaque area, carotid atherosclerotic plaque Course score, serum lipid levels, CRP, and adverse events rate (AER) were used as outcomes. Data from each RCTs were first pooled using random− effect pairwise meta− analyses and illustrated as odds ratios (ORs) or standardized mean differences (SMDs) with 95% confidence interval (CI). NMAs were performed using Stata17.0 software and the GeMTC package of R software to evaluate the comparative effectiveness of TCPMs, and displayed as ORs or SMDs with 95% CI. A Bayesian hierarchical random− effects model was used to conduct NMAs using the Markov Chain Monte Carlo algorithm. The GRADE partially contextualised framework was applied for NMA result interpretation. Results NMA included 27 RCT trials with 4131 patients and nine types of TCPMs. Pairwise meta− analyses indicated that Conventional Western medicine (CWM) + TCPM was superior to CWM in reducing the IMT (SMD: − 1.26; 95% CI − 1.59 to − 0.93), the carotid maximal plaque area (SMD − 1.27; 95% CI − 1.71, − 0.82) and the carotid atherosclerotic plaque Course score (SMD − 0.72; 95% CI 95% CI − 1.20, − 0.25). NMAs demonstrated that CWM + Jiangzhiling pill (JZL) with SUCRA 70.6% exhibited the highest effective intervention for reducing IMT. CWM + SXBX (Shexiang baoxin pill) was superior to other TCPMs in reducing the carotid maximal plaque area (83.0%), the atherosclerotic plaque Course score (92.5%), TC (95.6%) and LDL (92.6%) levels. CWM + NXT (Naoxintong capsule), CWM + XS (Xiaoshuang granules/enteric capsule), and CWM + ZBT (Zhibitai) were superior to other CPMs in improving TG (90.1%), HDL (86.1%), and CRP (92.6%), respectively. No serious adverse events were reported. Conclusions For CAP patients, CWM + XSBX was among the most effective in reducing carotid maximal plaque area, atherosclerotic plaque Course score, TC and LDL levels, and CWM + JZL was the most effective in reducing IMT. Overall, CWM + XSBX may be considered an effective intervention for the treatment of CAP. This study provides reference and evidence for the clinical optimization of TCPM selection in CAP treatment. More adequately powered, well− designed clinical trials to increase the quality of the available evidence are still needed in the future due to several limitations.